Fatal Cholestatic Hepatitis in an Infant: An Unusual Etiology - Mark R Oliver; Alfredo Pinto; R Brent Scott (Canadian Journal of Gastroenterology)
An infant girl who presented with cholestasis and hepatitis that rapidly progressed to fulminant liver failure is reported. Postmortem examination yielded a diagnosis of demonstrated extensive hepatic necrosis due to adenovirus type 5 infection which had developed in the setting of an occult primary immunodeficiency (severe combined immunodeficiency). The aim of this report is to alert the physician to a rare cause of cholestasis and hepatitis in infancy. Recognition of the combination of adenoviral infection with underlying primary immunodeficiency is a prerequisite to the provision of genetic counselling.